Initial training of teachers of History and Geography: their formative approaches, the construction of their pedagogical and professional knowledge. Analysis from the voices of the teaching staff in Chile (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
The article exposes the results of the research that sought to investigate the initial training of history teachers, geography, who will shed light on the characteristics of both the disciplinary and pedagogical approach in their training, the relevance of it, and how they build his pedagogical and professional knowledge. The analysis are carried out under a comprehensive-hermeneutic exercise, from a semi-structured interview applied to three history and geography teachers, from three universities with a tradition in the training of specialty teachers. The results show a strong disciplinary training, disjointed with the pedagogical training and the educational context; the privatization of the construction of pedagogical knowledge, and this, along with professional knowledge is built mainly from the epistemological concerns of the professor of history and geography, minimizing the influences of the educational context.
Keywords: History and Geography teachers; disciplinary training; pedagogical training; pedagogical knowledge; professional knowledge